2014
DOI: 10.1136/heartjnl-2014-305564
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester Acute Coronary Syndromes (MACS) decision rule for suspected cardiac chest pain: derivation and external validation

Abstract: ObjectiveWe aimed to derive and validate a clinical decision rule (CDR) for suspected cardiac chest pain in the emergency department (ED). Incorporating information available at the time of first presentation, this CDR would effectively risk-stratify patients and immediately identify: (A) patients for whom hospitalisation may be safely avoided; and (B) high-risk patients, facilitating judicious use of resources.MethodsIn two sequential prospective observational cohort studies at heterogeneous centres, we inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 31 publications
0
84
0
1
Order By: Relevance
“…The primary objective of the study was to validate a clinical decision rule, which has been reported separately (8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective of the study was to validate a clinical decision rule, which has been reported separately (8 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the emergency department (ED), 8 highsensitivity cardiac troponin has been shown to have greater diagnostic sensitivity at the time of presentation than standard assays (2 ). However, even with highsensitivity assays, use of the traditional diagnostic cutoff set at the 99th percentile yields a diagnostic sensitivity of only approximately 90% at the time of presentation, and many studies used less-sensitive gold standards as a comparator, possibly leading to inflated estimates of diagnostic sensitivity by this approach (3 ).…”
mentioning
confidence: 99%
“…Alternatives to this strategy have been proposed taking advantage of the fact that in patients with very low pre-test probability of AMI and Acute Coronary Syndrom (ACS), very low baseline cTn levels make the possibility of AMI highly unlikely [8,11,31,37]. If incorporated in the diagnostic pathway, such an early rule-out protocol could help avoid unnecessary tests and admissions for patients who do not have AMI but present with chest pain and have had cTn measured at presentation.…”
Section: Diagnostic Testing and Accuracy Of Troponin Testsmentioning
confidence: 99%
“…Project results indicated significant improvements in reducing the number of hospital admissions [28]). Finally, recent studies report that some low risk patients could be safely discharged on the basis of a single negative test if they present more than three hours after the onset of worst symptoms and have very low levels of cTn [8,11,31,37]. Our study aims to support EDs to effectively manage staff workload and to reduce the number of avoidable admissions from ED into hospital.…”
Section: Introductionmentioning
confidence: 99%
“…в последние годы появились диагностикумы для качественного определения уровня сердечного БСЖК и тропонина I. А в 2014 году в Ан-глии был разработан диагностический алгоритм MACS [18], в котором использована оценка клинических, электрокарди-ографических данных, а также определение уровня БСЖК и высокочувствительного тропонина для стратификации риска пациентов, доставленных в отделение скорой помощи с подо-зрением на острый коронарный синдром. По мнению авто-ров, данный протокол имеет преимущество для определения пациентов низкого риска в течение 4-часового временного окна с отрицательной предсказательной значимостью 99,8 %.…”
Section: резюме в статье представлено обсуждение проблемы выбора марunclassified